2021
DOI: 10.1152/ajplung.00440.2020
|View full text |Cite
|
Sign up to set email alerts
|

Balancing precision versus cohort transcriptomic analysis of acute and recovery phase of viral bronchiolitis

Abstract: Viral infections affecting the lower respiratory tract place enormous burdens on hospitals. As neither vaccines nor anti-viral agents exist for many viruses, understanding risk factors and outcomes in each patient using minimally invasive analysis, such as blood, can lead to improved healthcare delivery. A cohort of PAXGene RNAseq of infants admitted with moderate or severe acute bronchiolitis and respiratory syncytial virus (RSV) were compared with case-control statistical analysis and cohort-based outlier ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The phenotypes seen in the Geno2MP data suggested a broader analysis of CCR5 in disease pathologies. With the robust expression of CCR5 in blood and our history in studying the blood of immune challenged individuals, we selected to process CCR5 biology for blood-based RNAseq of 7,280 samples from 62 different BioProjects and three of our studies where we have patient-to-transcriptome insights ( 74 76 ) ( Figure 7 ). All these samples were blood collected into RNA PAXgene tubes to standardize sample collection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The phenotypes seen in the Geno2MP data suggested a broader analysis of CCR5 in disease pathologies. With the robust expression of CCR5 in blood and our history in studying the blood of immune challenged individuals, we selected to process CCR5 biology for blood-based RNAseq of 7,280 samples from 62 different BioProjects and three of our studies where we have patient-to-transcriptome insights ( 74 76 ) ( Figure 7 ). All these samples were blood collected into RNA PAXgene tubes to standardize sample collection.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest CCR5 levels in the MODS cohort were observed in sepsis patients, one of which (patient 27) was lethal. The RSV study’s top three outliers for CCR5 expression were all hospitalized RSV cases (patient 1, 4, 19) ( 76 ). Patient 1 had high levels of Agromyces aureus and Caulobacter vibrioides like reads in the blood in addition to clinically confirmed RSV, while also having multiple levels of elevated RNA associated with lung hyperinflammation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently little understanding of the gut microbiota composition of infants with RSV in the PICU. Through the use of blood transcriptomics, we have previously shown that members of this RSV cohort presented experienced an extensive inflammatory response [ 11 ]. Our focus here was to determine how severely RSV in hospitalized infants impacts the gut microbiota and how various exposures (antibiotics, diet) modulate the GI microbiota.…”
Section: Introductionmentioning
confidence: 99%